The Relationship Between Recreational Activity Participation and Vision Related Quality of Life Among Adults with Visual Impairment - Cuthrell, Betsy A. (East Carolina University, 2013)
The purpose of this study was to understand the relationship between number of activities individuals participated in, recreation participation frequency, and the meaning of recreational activity participation and factors associated with vision-related quality of life for adults with visual impairments. Thirty-five usable surveys were completed by visually impaired adults between the ages of 18 and 65, residing in the state of North Carolina. Quality of life was measured by the Vision Quality of Life Index (VisQOL). Results indicated there were significant relationship between quality of life, and the frequency, number of activities, and meaning of leisure activity engagement. Results of the study suggest that social activities had a positive effect on quality of life. Findings also suggest that participation in social activities was related to participation in other types of recreational activities. Research outcomes hold implications for service delivery demands and policy transformation for people with visual impairments in North Carolina. The results also indicate the need for further research in the areas of recreation activity participation, vision-related quality of life, and adults with visual impairments.
Keywords: Social research; Recreation and tourism; Recreation participation; Visual impairments; Visual quality of life; Quality of life; People with visual disabilities; Vision disorders; Recreation